Measuring Corporate Social Responsibility Performance for Employees with an NH Approach Method - Nor Hadi (IQTISHADIA, 2018)
This article explains the empirical research results of the social responsibility performance measurement model for employees that is done by companies by using the NH Approach method. Social responsibility needs to be measured to see the effectiveness of the social responsibility done by a company, as well as to provide legitimacy for stakeholders regarding the company’s volunteer efforts in carrying out its responsibilities. The NH Approach is an integrated social responsibility measurement model that was developed based on the legitimacy theory and the stakeholder theory. An evaluation is conducted from two sides, from the stakeholder side as the recipient of social responsibility assistance, and the company management side as the social responsibility assistance provider.The study used a research and development approach, where the respondents numbered 98 individuals with a response rate level of 92% (90 respondents who returned the questionnaires). From the 90 questionnaires submitted, only 62 of them were considered complete and analyzed.The research results reveal that the practice of social responsibility that was done by the company has a grade of Unsatisfactory (C), because the social responsibility index has a score of 62.39. Several factors act as the triggers, including misunderstandings between parties in understanding social responsibility, underdeveloped social responsibility programs that have already been conducted, and limited social responsibility practice, so that the programs implemented cover various elements of social responsibility.